2020
DOI: 10.1016/j.nima.2019.162432
|View full text |Cite
|
Sign up to set email alerts
|

Neutral bremsstrahlung in two-phase argon electroluminescence: further studies and possible applications

Abstract: We further study the effect of neutral bremsstrahlung (NBrS) in two-phase argon electroluminescence (EL), revealed recently in [1]. The absolute EL yield due to NBrS effect, in the visible and NIR range, was remeasured in pure gaseous argon in the two-phase mode, using a two-phase detector with EL gap read out directly by cryogenic PMTs and SiPMs. Possible applications of the NBrS effect in detection science are discussed, including those in two-phase dark matter detectors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…From Figures 4 and 9 one can see that NBrS EL, albeit being significantly weaker than ordinary EL above the Ar excitation threshold, has no threshold in electric field, in contrast to ordinary EL, and thus dominates below the threshold. Accordingly, the NBrS effect can explain two remarkable properties of proportional EL observed in experiment [9,13,19]: that of the photon emission below the Ar excitation threshold and that of the substantial contribution of the non-VUV spectral component above the threshold. ) and ionization ( ) (from [9], with permission from Elsevier).…”
Section: Electroluminescence Due Neutral Bremsstrahlung Effectmentioning
confidence: 86%
See 3 more Smart Citations
“…From Figures 4 and 9 one can see that NBrS EL, albeit being significantly weaker than ordinary EL above the Ar excitation threshold, has no threshold in electric field, in contrast to ordinary EL, and thus dominates below the threshold. Accordingly, the NBrS effect can explain two remarkable properties of proportional EL observed in experiment [9,13,19]: that of the photon emission below the Ar excitation threshold and that of the substantial contribution of the non-VUV spectral component above the threshold. ) and ionization ( ) (from [9], with permission from Elsevier).…”
Section: Electroluminescence Due Neutral Bremsstrahlung Effectmentioning
confidence: 86%
“…Their time constants are of 4.2 ns and 3.1 μs respectively: Figure 5. Summary of experimental data on reduced electroluminescence (EL) yield in gaseous Ar for all known (EL) mechanisms: for NBrS EL below 1000 nm, measured in [9,13] at 87 K; for ordinary EL in the VUV, due to excimer emission going via Ar * (3p 5 4s 1 ) excited states, measured in [9,13] at 87 K and in [14] at 293 K; for EL in the NIR due to atomic transitions going via Ar * (3p 5 4p 1 ) excited states measured in [15] at 163 K.…”
Section: Electroluminescence Due To Excimer Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the ordinary EL mechanism, a concurrent EL mechanism, based on bremsstrahlung of drifting electrons scattered on neutral atoms (so-called "neutral bremsstrahlung", NBrS), has been recently revealed [15,16]. It was shown that the NBrS effect can explain two remarkable properties of proportional electroluminescence: photon emission below the Ar excitation threshold and the substantial contribution of a non-VUV spectral component.…”
Section: Alternative Concepts Of Sipm-matrix Readout Of Two-phase Argon Detectorsmentioning
confidence: 99%